DE LA MODERNIZACIÓN AL AJUSTE ESTRUCTURAL: 30 AÑOS DE REVOLUCIÓN VERDE - Romero, Mayra (1994)
In 30 years of green revolution, from modernization time to nowadays structural adjusment, agricultural unequality has been deepened as well as the consequently precarious peasant condition, specially of those small producers.  To revert this process, there is a need of a decided policy, which can promote global participation on decisions related to agriculture and national production benefits.